2021
DOI: 10.47811/bhj.112
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of attempted suicide patients admitted in Jigme Dorji Wangchuck National Referral Hospital from January 2014 to September 2018

Abstract: Introduction: Attempted suicide is a major public health problem with a prevalence rate of approximately 2.7% worldwide. There is an increasing trend of attempted suicide in Bhutan. It is a strong clinical predictor of eventual suicide deaths and results in significant use of health care resources. This study aimed to describe the characteristics of attempted suicide patients admitted in Jigme Dorji Wangchuck National Referral Hospital from January 2014 to September 2018. Methods: This descriptive record revie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…It is felt that this result needs to be clarified in future studies. In a study by Letho et al (2017), a negative correlation was found between nurses' knowledge levels concerning suicide and their age. Also in this study, it was seen that there was no correlation between nurses' levels of knowledge concerning suicide and their gender.…”
Section: Discussionmentioning
confidence: 97%
See 4 more Smart Citations
“…It is felt that this result needs to be clarified in future studies. In a study by Letho et al (2017), a negative correlation was found between nurses' knowledge levels concerning suicide and their age. Also in this study, it was seen that there was no correlation between nurses' levels of knowledge concerning suicide and their gender.…”
Section: Discussionmentioning
confidence: 97%
“…In our study, the mean LOSS scores of nurses who had completed a master's degree were higher, although this was not statistically significant. Similarly, it was seen in the literature that as nurses' education levels rose, their levels of knowledge concerning suicide also rose (Letho et al, 2017;Sun et al, 2007). This may derive from nurses graduating from master's programs being more research oriented and from their having taken more classes on psychiatric nursing (Finkelman & Kenner, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations